Correlação entre a resistência à corrosão e as tensões residuais de um aço inoxidável lean duplex uns s32304 submetido à processo de soldagem TIG e diferentes condições de tratamentos térmicos e resfriamento - Merlo, Panmela Pereira (2016)
Heat treatment and welding process can promote the precipitation of secondary phases in duplex stainsless steels, resulting in the phenomenon ofsensitization,whichis detrimental tothecorrosion resistance of the material. In this work, the UNS S32304 steel samples were subjected to heat treatments at temperatures of 475, 600 and 750 ° C for 8 hours, air or seawater cooled and the GTAW welding process followed by the same treatments. In order to evaluate the resistance to localized corrosion were performed electrochemical tests of the type DL-EPR. After DL-EPR was possible to calculate the degree of sensitization(DOS) of the samples and it was found in general that the elevated heat treatment temperature caused an increase in localized corrosion. The samples subjected to the welding processand heat treatment had a superior sensitizationthan the samplestreated only, and that the cooledair obtained DOS higher than cooled in seawater. The residual microstressesin ferrite introduced a compatible DOSbehavior in only treated samples